Enhancing CSR disclosure through foreign ownership, foreign board members, and cross-listing : Does it work in Russian context? - Garanina, Tatiana; Aray, Yulia (Elsevier, 2021)
This paper examines whether foreign shareholders, foreign board members, and cross-listing, are related to corporate social responsibility (CSR) disclosure in Russia. A sample of 223 Russian listed companies is analyzed for the period 2012–2015. In line with legitimacy theory and agency theory, our empirical results demonstrate that foreign board members and cross-listing help companies to raise their accountability through increased CSR disclosure. At the same time we report that foreign ownership does not enhance CSR disclosure, as the majority of foreign shareholders of Russian companies are registered in offshore domiciles that are used for more efficient tax allocation.
Keywords: Corporate governance; Foreign board of directors; Cross-listing; Corporate social responsibility; Russia; foreign ownership; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|